Microlenses for stereoscopic image formation - Rocha, R. P. (2012)
This paper presents microlenses for integration on a stereoscopic image sensor in CMOS technology for use in biomedical devices. It is intended to provide an image sensor with a stereoscopic vision. An array of microlenses potentiates stereoscopic vision and maximizes the color fidelity. An array of optical filters tuned at the primary colors will enable a multicolor usage. The material selected for fabricating the microlens was the AZ4562 positive photoresist. The reflow method applied to the photoresist allowing the fabrication of microlenses with high reproducibility.